2011
DOI: 10.1590/s2179-64912011000300007
|View full text |Cite
|
Sign up to set email alerts
|

Aplicação do teste M1-Alpha em sujeitos normais com baixa escolaridade: estudo piloto

Abstract: OBJETIVO: Verificar o desempenho de sujeitos normais com baixa escolaridade no teste M1-Alpha e obter parâmetros que possam ser utilizados na avaliação clínica de pacientes afásicos com baixa escolaridade, expostos a este teste. MÉTODOS: Foram selecionados 30 sujeitos normais de baixa escolaridade (um a quatro anos de estudo), com idade superior a 18 anos e inferior a 60 anos, sendo 15 do gênero masculino e 15 do gênero feminino. Todos foram submetidos à aplicação do teste M1-Alpha, que comporta entrevista sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Likewise, other studies have shown the importance of the number of years of formal education in language tasks, with findings similar to those observed in the present study. 1,6,[8][9][10]33 As seen in the results, in this study there was a moderate positive correlation with education in tasks that involve dictation, written naming, written comprehension, auditory comprehension and written narrative. These tasks require reading-writing abilities that are developed over the course of education.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Likewise, other studies have shown the importance of the number of years of formal education in language tasks, with findings similar to those observed in the present study. 1,6,[8][9][10]33 As seen in the results, in this study there was a moderate positive correlation with education in tasks that involve dictation, written naming, written comprehension, auditory comprehension and written narrative. These tasks require reading-writing abilities that are developed over the course of education.…”
Section: Discussionsupporting
confidence: 72%
“…Previous research has shown that tasks involving graphic stimuli (written comprehension, dictation, reading, written naming, number dictation, reading of numbers, written narrative and written text comprehension) tend to be more sensitive to the influence of education. 6,8,11 The importance, albeit weaker, of FRWH in linguistic performance deserves to be highlighted, given that it increases the predictive power of the education variable. Regularly practicing reading and writing can compensate for low education levels in linguistic performance, 17,33 and the quality of what is read is one of the biggest predictors of cognitive performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been stated that the BDAE would be sensitive to demographic variables, particularly to information regarding years of schooling 17 . Data show that 27% of Brazilians in between 15 and 64 years of age were classified as illiterate in 2009, while another 14% are functionally illiterate, which says that 41% of the population cannot read or understand what is being read 21,22 .…”
Section: Methodsmentioning
confidence: 99%
“…As can be seen regarding the batteries for Language assessment and diagnosis of aphasia (profile and severity), there is the Montreal-Toulouse protocol, in brief and expanded versions. 34 - 37 This protocol has undergone the steps of psycholinguistic and cultural adaptation of linguistic and pictorial items, evaluation of psychometric properties/diagnostic validity and standardization, and is soon to be marketed in Brazil (MTL Brasil, Parente et al, manuscript not published). This instrument includes tasks assessing automatic language, auditory and written comprehension, oral and written speech (discourse), writing to dictation and copy, oral repetition, reading, verbal fluency, naming, calculus, object manipulation, non-verbal praxis and arithmetic skills.…”
Section: Current Panoramamentioning
confidence: 99%